The Influence of South Africa’s Democratic Principles on its Cybersecurity Framework and Cyber Threat Response - Venencia Paidamoyo Nyambuya; Nirmala Devi Gopal (Journal of BRICS Studies)
This study explores the intricate relationship between South Africa's democratic political system, its commitment to human and private rights, and the development of its cybersecurity framework, strategy, and response to cyber threats. Given the country's robust constitutional commitment to human rights, this research explores how these democratic principles are integrated into and influence cybersecurity policies and practices. Through a comprehensive analysis of legislative documents, policy frameworks, this study identifies the extent to which democratic values and human rights considerations shape South Africa's approach to cybersecurity.